2015
DOI: 10.1242/jeb.111864
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial light affects the expression of brain encephalopsin and plasma monoamine concentration in the mouse

Abstract: Encephalopsin (OPN3) belongs to the light-sensitive transmembrane receptor family mainly expressed in the brain and retina. It is believed that light affects mammalian circadian rhythmicity only through the retinohypothalamic tract, which transmits light information to the suprachiasmatic nucleus in the hypothalamus. However, it has been shown that light penetrates the skull. Here, we present the effect of transcranial light treatment on OPN3 expression and monoamine concentrations in mouse brain and other tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…It should be remembered that mice are nocturnal animals and the ML group was illuminated in the beginning of their resting state, which might disturb the circadian rhythm and stress the animals. We have previously published results regarding the effects of transcranial light on monoamine concentrations in plasma and adrenal gland samples [20]. We showed that the levels of dopmanine and noradrenaline increased, and the levels of adrenaline decreased with transcranially illuminated mouse [20].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…It should be remembered that mice are nocturnal animals and the ML group was illuminated in the beginning of their resting state, which might disturb the circadian rhythm and stress the animals. We have previously published results regarding the effects of transcranial light on monoamine concentrations in plasma and adrenal gland samples [20]. We showed that the levels of dopmanine and noradrenaline increased, and the levels of adrenaline decreased with transcranially illuminated mouse [20].…”
Section: Discussionmentioning
confidence: 80%
“…Since OPN4 is known to have an important role in light transmission through the eyes, and on the other hand, OPN4 is shown to be expressed in the hypothalamus [27], it may be capable of activating circadian signaling pathways directly by transcranially penetrated light, although we acknowledge that there might be some light transmitted through the transcranially illuminated ocular photoreceptors [49,50]. Even though the absorption maximum of our light source (450 nm) [20] was not optimal for the OPN4 expression maximum (476 -484 nm) [51,52], we were able to obtain significant results in this study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations